Students' knowledge and attitude concerning organ donation at Iraqi nursing colleges - Haider Mohammed Majeed; Ahmed Fleih Hassan; Ayad Majid Mousa (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Organ transplantation is an effective therapy for end-stage organ failure. However, there is a large gap between the need for and the supply of donor organs. OBJECTIVES: This study aimed to assess nursing students' knowledge and attitudes about organ donation. MATERIALS AND METHODS: This is a descriptive cross-sectional design study. The study was conducted at four faculties of nursing, which were Baghdad, Misan, Tikrit, and Kirkuk in Iraq. The three tools included are as follows: I: Socio-Demographic Questionnaire; II: Organ-Tissue Donation and Transplantation Knowledge Scale (ODTKS); and III: Organ Donation Attitude Scale (ODAS). RESULTS: More than two-thirds (71%) of the studied students have an accepted level of knowledge, while 70% of the studied students had a positive attitude toward organ donation and transplantation. There were statistically significant differences (P- value <0.05) between socio-demographic characteristics and knowledge level regarding gender, marital status, and academic year. Also, there were significant differences between socio-demographic characteristics and students' attitude levels regarding gender and academic year. CONCLUSION: More than two-thirds of students had a good and fair level of knowledge and a positive attitude toward organ donation and transplantation. Providing lectures within the curriculum is needed for students to raise their knowledge and attitude about organ transplantation and donation.